BeeHeal: promoting bee health for sustainable agriculture - Martín-Hernández, Raquel (2018)
During the last years there is an alarming increase in the collapse of honeybee colonies (Apis mellifera) where bee parasites and pathogens like Varroa destructor mites, the microsporidia Nosema ssp. and viruses have played the leading role. Colony decline might compromise not only food security but also present and future income to the growers. Hence, four institutions from Mediterranean area have joined forces to put toghether a project entitled, “BEEHEAL: Promoting bee health for sustainable agriculture”. BEEHEAL is a collaborative research between Centro de Investigación Apícola y Agroambiental de Marchamalo - CAR (Spain), Centre de recherche Provence-Alpes-Côte d’Azur Unité: Abeilles et Environnement - INRA (France), Agricultural Research Organization, The Volcani Center - ARO (Israel) and Mountain Research Center (CMO), Polytechnic Institute of Bragança (Portugal). The aim of this project is to determine the phenology and interaction of the microsporidia Nosema ceranae and viruses including acute bee paralysis virus (ABPV), Israeli acute paralysis virus (IAPV), Black queen cell virus (BQCV) Chronic bee paralysis virus (CBPV) and Deformed wing virus (DWV), in Spain, France, Portugal and Israel. The findings of this project, which involves an active and unique cooperation among partners representing Mediterranean countries which encompasses a wide range of environmental and beekeeping management conditions, will contribute to ameliorate the damage caused by the expansion of N. ceranae through a rational implementation of existing treatments to avoid emergence of synergistic pathogens that accelerate colony collapse compromising food security. This project started at 2017 and it will end in 2020. BEEHEAL is funded through the ARIMNet2 (2016) Call by the following funding agencies: INIA (Spain), ANR (France), MOARD (Israel), and FCT (Portugal). This presentation will detail the tasks that are ongoing in the BEEHEAL project.